Microstructural characterization of multiple sclerosis lesion phenotypes using multiparametric longitudinal analysis - Ravano, Veronica; Andelova, Michaela; Piredda, Gian Franco; Sommer, Stefan; Caneschi, Samuele; Roccaro, Lucia; Krasensky, Jan; Kudrna, Matej; Uher, Tomas; Corredor-Jerez, Ricardo A; Disselhorst, Jonathan A; Maréchal, Bénédicte; et al. (Journal of neurology, 2024)
BACKGROUND AND OBJECTIVES: In multiple sclerosis (MS), slowly expanding lesions were shown to be associated with worse disability and prognosis. Their timely detection from cross-sectional data at early disease stages could be clinically relevant to inform treatment planning. Here, we propose to use multiparametric, quantitative MRI to allow a better cross-sectional characterization of lesions with different longitudinal phenotypes. METHODS: We analysed T1 and T2 relaxometry maps from a longitudinal cohort of MS patients. Lesions were classified as enlarging, shrinking, new or stable based on their longitudinal volumetric change using a newly developed automated technique. Voxelwise deviations were computed as z-scores by comparing individual patient data to T1, T2 and T2/T1 normative values from healthy subjects. We studied the distribution of microstructural properties inside lesions and within perilesional tissue. RESULTS AND CONCLUSIONS: Stable lesions exhibited the highest T1 and T2 z-scores in lesion tissue, while the lowest values were observed for new lesions. Shrinking lesions presented the highest T1 z-scores in the first perilesional ring while enlarging lesions showed the highest T2 z-scores in the same region. Finally, a classification model was trained to predict the longitudinal lesion type based on microstructural metrics and feature importance was assessed. Z-scores estimated in lesion and perilesional tissue from T1, T2 and T2/T1 quantitative maps carry discriminative and complementary information to classify longitudinal lesion phenotypes, hence suggesting that multiparametric MRI approaches are essential for a better understanding of the pathophysiological mechanisms underlying disease activity in MS lesions.
Keywords: Magnetic Resonance Imaging; mozek; magnetická rezonanční tomografie; Humans; Longitudinal Studies; Enlarging lesions; lidé středního věku; Multiple Sclerosis; Disease Progression; Lesion subtyping; Female; multiparametrická magnetická rezonance; dospělí; Phenotype; lidé; Relaxometry; Adult; Multiple sclerosis; ženské pohlaví; longitudinální studie; roztroušená skleróza; Male; Quantitative MRI; Middle Aged; Brain; fenotyp; Multiparametric Magnetic Resonance Imaging; Cross-Sectional Studies; progrese nemoci; mužské pohlaví; průřezové studie